(untitled) (A+BE | Architecture and the Built Environment, 2022)
This thesis examines the energy performance of dwellings of Dutch non-profit housing associations towards a future sustainable housing stock. Improving the energy performance of dwellings aims to improve the quality of dwellings and therewith to lower the actual energy consumption. Lowering the actual energy consumption of dwellings contributes to the battle against climate change. This thesis addresses four studies. Study 1 assesses the energy performance progress of over two million dwellings of Dutch non-profit housing associations between 2017 and 2020. It gives insights into the development of the housing stock, the effect of changes of and within the stock, the effect of characteristics of housing associations and it relates the improvement of the energy performance to the sectoral goal. Study 2 assesses advanced models to improve estimations of actual energy consumption of dwellings and therewith to better estimate the effect of renovation measures on actual energy savings. Study 3 assesses the energy performance of dwellings with heat pumps. It gives insights into the energy performance of dwellings with heat pumps as a promising renovation measure towards a future sustainable housing stock. Study 4 assesses the process to create a model to benchmark the energy performance in a changing policy context. The four studies contribute to the understanding of the improvement of the energy performance of dwellings of non-profit housing associations towards a future sustainable housing stock.